Community-Level Economic Distress, Race, and Risk of Adverse Outcomes After Heart Failure Hospitalization Among Medicare Beneficiaries. Issue 2 (11th January 2022) - Mentias, Amgad; Desai, Milind Y.; Vaughan-Sarrazin, Mary S.; Rao, Shreya; Morris, Alanna A.; Hall, Jennifer L.; Menon, Venu; Hockenberry, Jason; Sims, Mario; Fonarow, Gregg C.; Girotra, Saket; Pandey, Ambarish
Abstract : Background: Socioeconomic disadvantage is a strong determinant of adverse outcomes in patients with heart failure. However, the contribution of community-level economic distress to adverse outcomes in heart failure may differ across races and ethnicities. Methods: Patients of self-reported Black, White, and Hispanic race and ethnicity hospitalized with heart failure between 2014 and 2019 were identified from the Medicare MedPAR Part A 100% Files. We used patient-level residential ZIP code to quantify community-level economic distress on the basis of the Distressed Community Index (quintile 5: economically distressed versus quintiles 1–4: nondistressed). The association of continuous and categorical measures (distressed versus nondistressed) of Distressed Community Index with 30-day, 6-month, and 1-year risk-adjusted mortality, readmission burden, and home time were assessed separately by race and ethnicity groups. Results: The study included 1 611 586 White (13.2% economically distressed), 205 840 Black (50.6% economically distressed), and 89 199 Hispanic (27.3% economically distressed) patients. Among White patients, living in economically distressed (versus nondistressed) communities was significantly associated with a higher risk of adverse outcomes at 30-day and 1-year follow-up. Among Black and Hispanic patients, the risk of adverse outcomes associated with living in distressed versus nondistressed communities was not meaningfully different at 30 days and became more prominent by 1-year follow-up. Similarly, in the restricted cubic spline analysis, a stronger and more graded association was observed between Distressed Community Index score and risk of adverse outcomes in White patients (versus Black and Hispanic patients). Furthermore, the association between community-level economic distress and risk of adverse outcomes for Black patients differed in rural versus urban areas. Living in economically distressed communities was significantly associated with a higher risk of mortality and lower home time at 1-year follow-up in rural areas but not urban areas. Conclusions: The association between community-level economic distress and risk of adverse outcomes differs across race and ethnic groups, with a stronger association noted in White patients at short- and long-term follow-up. Among Black patients, the association of community-level economic distress with a higher risk of adverse outcomes is less evident in the short term and is more robust and significant in the long-term follow-up and rural areas. Abstract : Supplemental Digital Content is available in the text.